BELUM TERCAPAINYA INDIKATOR STANDAR PELAYANAN MINIMAL PROGRAM KESEHATAN IBU DAN ANAK (KIA) Studi Kualitatif di Puskesmas Sei Rampah, Kabupaten Serdang Bedagai, Tahun 2021) - Desy Lustiyani Rajagukguk; Myrnawati Crie Handini; Kesaktian Manurung; Mido Ester J. Sitorus (Universitas Pahlawan, 2022)
The purpose of this research is to explore more deeply about all matters related to the lack Minimum Service Standards (MSS) indicators for Maternal and Child Health Program (KIA) at Sei Rampah Public Health Center, Serdang Bedagai Regency. This research is a qualitative research. The research instrument is the researcher himself who is subjective, so the data obtained is checked for validity using the triangulation technique, namely by extending the time ,source triangulation and triangulation of data collection methods. The informant is the head of the public health center, Coordinator midwives, implementing midwives, nurses and pregnant mother. Data analysis was carried out using the Miles and Hubberman method. The results of research showed the indicators for the Minimum Service Standards for the Maternal and Child Health Program (KIA) at the Sei Rampah Health Center had not reached the 100% target and the lowest indicator coverage was the Indicator Detection of Risk Factors and Complications 17,3%. The reason for not achieveing the SPM for KIA program because the People are hesitant to check their health at the Public health center during the Covic-19 pandemic. The efforts made by the Public health centre management are by increasing the number of midwives, doing home-care, providing information to the community, either by banners or leaflet about the implementation of health services at the puskesmas, carrying out health shipping in accordance with the Covid 19 health protocol procedures. This study produces a Theoritical Framework based on results of data collection, processing and analysis.